PERAN FLYER SEBAGAI MEDIA PROMOSI PESTA PERKAWINAN CINA BENTENG - Lidiana, Dian; Firmansyah, Imam (Universitas Mercu Buana, 2023)
Cina Benteng community in Tangerang consists of people of Chinese descent who have mixed with the indigenous community. Their wedding was enlivened by a variety of acculturated arts, such as chiautaw, Gambang Kromong, and Cokek. Surprisingly, the wedding party is accessible to the general public, and anyone is welcome to join without an invitation. It is believed that the more guests who come, the more blessings they will bring. Cina Benteng community has promotional media in the version of prints called flyers. This media contains wedding information for one year. This research looks at how flyer can be used to promote weddings in the Cina Benteng community. The research method used is qualitative and descriptive approach. The data was collected through a review of the literature, observation, interviews, and documentation. According to the result of this research, flyers are the main source of information for invited guests, tukang plesir, and wayang cokek. The flyer is the only source of information for all parties interested in attending the wedding ceremony of the Cina Benteng community.